Jewelry by Suzanne Belperron "my style is my signature" - Corbett, Patricia, 1951-; Landrigan, Ward; Landrigan, Nico; Lagerfeld, Karl (London Thames & Hudson, 2015)
In 1919 Suzanne Belperron began her lifelong journey designing jewelry so unique she rarely signed her name to it; her colourful compositions of gems and pure, sensual, organic forms became her unmistakable trademark, recognizable at a glance. Illustrated here is a splendid array of Belperrons work, from the earliest sketches made while she was a student and designs made for Rene Boivin in the 1920s and 1930s to the original designs she created for Hollywood clientele such as Clark Gable, Fred Astaire, Frank Sinatra and Lauren Bacall as well as fashion icons and the cream of British aristocracy. Numerous hand-coloured drawings and original designs, selected from the largest archive of her work (nearly all unpublished), are matched with an impressive range of finished pieces. Part 1 follows Belperrons rise to fame in six chapters based on private records from the Belperron family and those of the expert craftsmen with whom she collaborated. Part II presents a portfolio of some of the rarest, most delicate and most refined examples of her work, combined with the best of over 4,000 sketches from the Belperron Archive. This is the complete and indispensable guide to the jewelry marque that defined modern French chic.
Includes bibliographical references (page 232-233) and index.
Keywords: Belperron, Suzanne -- 1900-1983.; Jewelry -- Design -- History -- 20th century. -- France; Jewelers -- France -- Biography